Intuitionistic Fuzzy R0 Bitopological Space: An In-depth Exploration - Miah, Saikh Shahjahan; Jumur, Badrun Naher (GANIT: Journal of Bangladesh Mathematical Society, 2024)
We popose intuitionistic fuzzy bitopological R0-spaces (abbreviated IFB-R0) in this study. On intuitionistic fuzzy bitopological space, we introduce several new ideas of R0-space. Our notions are maintained under one-one, onto, fuzzy open, and fuzzy continious mappings, and we demonstrate that R0-spaces satisfy the "good extention" property. GANIT J. Bangladesh Math. Soc. 44.1 (2024) 23- 28